A critical review of the incidence and risk factors for finger injuries in rock climbing - Jones, G.; Johnson, M. I. (Current Sports Medicine Reports, 2016)
Rock climbing is a popular sporting activity and indoor sport climbing has been accepted for inclusion in the 2020 Olympic Games. The aim of this article is to critically review research on the incidence and risk factors associated with injuries during rock climbing. A semisystematic approach in reviewing literature on incidence and prevalence was applied. Articles were identified after searches of the following electronic databases: Discover, Academic Search Complete (EBSCO), PubMed, Embase, SPORTDiscus, and ScienceDirect. Despite methodological shortcomings of the studies contained within the review, the frequency of climbing-related injuries is high and can be challenging to diagnose. The fingers are the most common site of injury with previous injury a significant risk factor for reinjury. The annular pulleys of the fingers are the most commonly injured structure and evidence suggests epiphyseal fractures in adolescent sport climbers is increasing. A diagnostic and therapeutic algorithm for climbing-related finger injuries is proposed.